Corporate Governance Characteristics and Discretionary Accruals Among Non-Financial Firms Listed in Nairobi Securities Exchange - Edwin Sitienei (International Journal of Management, Accounting and Economics, 2023)
This study explores the relationship between corporate governance traits and discretionary accruals among non-financial firms listed in NSE. Our study discovered that the board size has a relatively insignificant negative impact on the discretionary accruals of non-financial firms listed in the NSE using a sample of 44 publicly traded non-financial firms based on 2012-2021 data. The findings on board independence indicate a significant positive relationship at 10% significance. The results suggest that board independence doesn't reduce discretionary accruals in non-financial firms listed in NSE Kenya. The CEO duality, on the other hand, revealed a statistically positive insignificant effect on discretionary accruals, contrary to expectations. The research findings also pointed to income-decreasing accruals earnings management as depicted by a mean of -.083 discretionary accruals in the descriptive statistics. On the effects of board meetings on discretionary accruals, the study found an insignificant negative relationship. The findings of this study may be useful for regulators to re-evaluate their laws and mandates regarding firms and their corporate governance structure, as well as for legislators who have the power to nominate board members to select competent and knowledgeable personnel.